Performance Evaluation of a Typical 50kWp Solar Park Village Energy Option in Cameroon - Tangka, Julius K.; Besong, Mbi B; Djoukeng, Henri Grisseur (European Journal of Applied Sciences, 2023)
The Cameroon government brought up a project of decentralized off grid rural electrification using 50kW solar parks in some villages to curb the rampant power outages experienced in the country. Over 1000 of such plants are to be installed in the country. The first 50 were already installed since 2017 but no performance evaluation has been carried out to investigate if this option satisfies the aspiration of the users. Performance evaluation was carried out on a 50kW solar powered mini off-grid system in Cameroon, a module adopted by the government to solve rural electricity crises. The evaluation involved investigating the production conformity with design parameters and socioeconomic sustainability of the project. The system is made of 200 modules of 250 Wp and 192 batteries of 2 V/800 Ah each. The study involved monitoring the array, the final and reference yields, energy losses, and the performance ratio. During this period, the system produced an average daily energy generation of 73.04 kWh and 44.72 kWh as daily energy consumption with an average performance ratio of 17.10 % and capacity utilization factor of 6.07 %. The average reference yield, array yield, final yield, array capture loss and system loss for the system were of 5.23, 1.46, 0.66, 3.77 and 0.57 h/d respectively. Average array, inverter and system efficiencies were 42.83 %, 61.24 % and 26.23 % respectively. The results obtained show that for this location, about 25 % of the energy produced is not consumed even as the plant is not functioning to its full capacity. It was recommended that government should make a detailed feasibility study establishing the load consumption ability and the power curve of each village before doing the installations.